Spatial Distribution of Trypanosomes in Cattle From Western Kenya - Kivali, Velma; Kiyong'a, Alice N.; Fyfe, Jenna; Toye, Philip; Fèvre, Eric M.; Cook, Elizabeth A. J. (Frontiers in Veterinary Science, 2020)
African Animal Trypanosomiasis (AAT) is a tsetse-transmitted protozoan disease endemic in “the tsetse belt” of Africa. Past studies investigating the epidemiology of the disease rarely focused on spatial distribution when reporting the prevalence. The challenge of understanding the spatial epidemiology of the disease is further confounded by low-sensitive parasitological techniques used in field investigations. This study aimed to identify trypanosome species in cattle and their spatial distribution in western Kenya. Low-sensitive microscopic analysis and highly-sensitive polymerase chain reaction (PCR) techniques were also compared to better understand the epidemiology of Trypanosoma infections by use of the geographical information system (GIS). Blood samples from 888 cattle, collected between August 2010 and July 2012, were examined for Trypanosoma parasites by light microscopy and PCR. The spatial distribution of Trypanosoma positive cases by species were mapped and overlaid on the map for tsetse distribution. The estimated prevalence was 4.17% by PCR compared to 2.48% by microscopy. Trypanosomes were detected in tsetse free areas. T.vivax and T. b. brucei were identifed, but not the zoonotic T. b. rhodesiense. This study demonstrated the importance of geospatial data analysis to understand the epidemiology of the parasite, to inform future research and formulate control strategies.